Ceramic matrix composite material and preparation method thereof
By preparing porous ceramic precursors and performing resin penetration and temperature isostatic pressure treatment, the problem of insufficient impact resistance and texture of existing mobile phone backplane materials is solved, and the high fracture toughness, impact resistance and thermal conductivity of ceramic matrix composite materials are achieved. Rate.
Patent Information
- Application Number
- CN202411710419.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing mobile phone back panel materials have shortcomings in impact resistance and texture, especially the fragile glass, poor texture of resin-based fiber reinforced composite materials and poor puncture resistance.
By using the preparation method of ceramic matrix composite materials, the fracture toughness and impact resistance of the material are improved by preparing porous ceramic precursors and permeating resins, combined with temperature isostatic pressure treatment.
The fracture toughness, impact resistance and thermal conductivity of ceramic matrix composite materials are significantly improved, forming composite materials with relatively low density but excellent performance.
Smart Images

Figure BDA0005155558940000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a ceramic-based composite material and a preparation method thereof. Background Art
[0002] As consumers continue to pursue the functional practicality, fashionable aesthetics, grip comfort and long-term durability of mobile phone appearance, the back panel of the mobile phone, as the appearance part that consumers directly touch and intuitively feel, is an important part that can best reflect the texture and attractiveness of the product. The materials used have gradually changed from the earliest plastics (PC, PMMA / PC) to light and thin, high-strength aluminum alloys; and with the advent of the 5G era, metal back panels have begun to be replaced by back panels of materials such as microcrystalline glass, ceramics, and fiberglass boards in recent years because of their shielding effect on mobile phone signals. Although glass can be processed to obtain a good frosted texture, it is very brittle, has low impact resistance, and is prone to cracks when dropped. Resin-based fiber-reinforced composite materials have the characteristics of lightness, high toughness, and high strength, but their texture is basically the same as plastic, and leather is often required to improve their grip comfort, and their puncture resistance is poor.
[0003] In view of this, a method for preparing a composite material that has texture, good fracture toughness and impact resistance and can be applied to the back cover of a mobile phone is particularly necessary. Summary of the invention
[0004] The purpose of the present invention is to provide a ceramic-based composite material and a preparation method thereof, which is beneficial to improving the fracture toughness and impact resistance of the ceramic material.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material, comprising:
[0007] Prepare a ceramic slurry, wherein the ceramic slurry includes a premix, a powder mixture, a catalyst and an initiator, the powder mixture includes a ceramic powder and a sintering aid, and the premix includes an organic monomer, a cross-linking agent, a solvent, a dispersant and a pH adjuster;
[0008] A porous ceramic precursor is prepared, the ceramic slurry is poured into a mold, and then the ceramic slurry is dried and demolded to obtain a green body; the green body is subjected to cold isostatic pressing, debinding and sintering in sequence to obtain the porous ceramic precursor;
[0009] Resin infiltration, placing the porous ceramic precursor in a resin, allowing the resin to infiltrate the porous ceramic precursor, to obtain a resin-infiltrated porous ceramic precursor;
[0010] The resin-infiltrated porous ceramic precursor is subjected to warm isostatic pressing to obtain a ceramic-based composite material.
[0011] In an optional embodiment, the ceramic powder is selected from at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide and zirconium oxide;
[0012] and / or, the sintering aid is selected from at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide and strontium oxide;
[0013] And / or, in the powder mixture, the mass fraction of the ceramic powder is 92wt.% to 100wt.%;
[0014] and / or, the particle size of the powder mixture is 0.9 μm to 25 μm;
[0015] And / or, the preparation of the powder mixture includes: ball milling and drying a mixture including the ceramic powder, sintering aid and ball milling aid to obtain the powder mixture; in the ball milling step, the mass ratio of grinding balls, powder mixture and ball milling aid is 9-11:1:1.5-2.5, the ball milling speed is 180rpm-250rpm, and the ball milling time is 10h-20h.
[0016] In an optional embodiment, the total mass fraction of the organic monomer and the cross-linking agent in the premix is 11wt.% to 21wt.%, the mass ratio of the organic monomer and the cross-linking agent is (10 to 23):1, the mass fraction of the dispersant is 0.3wt.% to 3.5wt.%, the mass fraction of the catalyst is 0.01wt.% to 0.10wt.%, and the pH value of the premix is 9 to 12;
[0017] And / or, the organic monomer is selected from at least one of dimethyl acrylamide and isobutylene-maleic anhydride copolymer;
[0018] And / or, the cross-linking agent is selected from at least one of methylenebisacrylamide and isobutylene-maleic anhydride copolymer;
[0019] and / or, the dispersant is selected from at least one of ammonium polyacrylate, polyethylene glycol and ammonium citrate;
[0020] And / or, the pH adjuster is aqueous ammonia.
[0021] In an optional embodiment, the mass fraction of the initiator in the ceramic slurry is 0.03wt.% to 0.16wt.%;
[0022] And / or, the mass fraction of the catalyst in the ceramic slurry is 0.01wt.% to 0.10wt.%;
[0023] And / or, the initiator is ammonium persulfate;
[0024] And / or, the catalyst is tetramethylethylenediamine;
[0025] And / or, the solid content of the ceramic slurry is 40% to 70%;
[0026] And / or, the viscosity of the ceramic slurry is 30 mPa·s to 100 mPa·s;
[0027] And / or, the preparation of the ceramic slurry includes: ball milling a mixture including the powder mixture and the premixed liquid, and then adding a catalyst and an initiator to obtain the ceramic slurry.
[0028] In an optional embodiment, in the step of preparing the porous ceramic precursor, the ceramic slurry is first vacuum degassed, and a water-based release agent is applied to the molding surface of the mold, and then the degassed ceramic slurry is poured into the mold;
[0029] And / or, the drying temperature is 40°C to 70°C, and when the weight loss of the mold for pouring the ceramic slurry is 25% to 30%, the temperature is lowered to 30°C to 50°C, and the temperature is kept for 2 to 5 hours, and then demoulding;
[0030] And / or, during the cold isostatic pressing treatment, the applied pressure is 10 MPa to 200 MPa, and the holding time is 10 min to 20 min; preferably, the applied pressure is 45 MPa to 160 MPa;
[0031] And / or, in the debinding step, the temperature is first kept at 300°C to 350°C for 0.5h to 2h, and then kept at 500°C to 540°C for 0.5h to 2h, with a heating rate of 1°C / min to 5°C / min;
[0032] And / or, the heating rate before sintering is 0.5℃ / min~1℃ / min, the sintering temperature is 1300℃~1550℃, and the insulation time is 2~4h; after the insulation is completed, the furnace temperature is reduced to 500℃ at 1℃ / min, and then cooled to room temperature with the furnace.
[0033] In an optional embodiment, the porous ceramic precursor is mechanically processed before resin infiltration.
[0034] and / or, first degassing the resin, and then placing the porous ceramic precursor in the resin;
[0035] In an optional embodiment, the method for preparing the resin comprises: mixing a curing agent and a mixed solution for 3 hours to 4 hours to obtain the resin, wherein the mixed solution comprises at least one of dimethacrylate urethane, methyl methacrylate, polyacrylic acid or triethylene glycol dimethacrylate;
[0036] And / or, the curing agent is selected from at least one of benzoyl peroxide and butanone peroxide;
[0037] And / or, the mass fraction of benzoyl peroxide in the resin is 0.2wt.% to 1wt.%;
[0038] And / or, the mass fraction of butanone peroxide in the resin is 0.4wt.% to 2wt.%.
[0039] In an optional embodiment, in the resin infiltration step, the environment in which the resin immerses the porous ceramic precursor is alternately evacuated and pressurized to promote the resin to infiltrate the porous ceramic precursor;
[0040] And / or, the vacuuming step is to vacuumize to a pressure less than 0.1 Pa;
[0041] And / or, the pressurizing step is to pressurize to a pressure of 1 MPa to 3 MPa and maintain for 30 min to 80 min;
[0042] And / or, the vacuuming and pressurizing steps are performed 5 to 7 times.
[0043] In an optional embodiment, during the warm isostatic pressing treatment, the pressure applied is 90 MPa to 300 MPa, the temperature is 75° C. to 90° C., and the holding time is 2 h to 4 h.
[0044] In a second aspect, the present invention provides a ceramic-based composite material prepared by the method described in any one of the aforementioned embodiments.
[0045] The present invention has the following beneficial effects:
[0046] The present application first prepares a porous ceramic precursor, and the porous structure effectively reduces its density; then resin infiltration is performed, and the infiltrated resin can significantly improve the fracture toughness, impact resistance and thermal conductivity of the porous ceramic precursor matrix without significantly increasing the density of the composite material. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0048] An embodiment of the present invention provides a method for preparing a ceramic-based composite material, comprising:
[0049] Prepare a ceramic slurry, wherein the ceramic slurry includes a premix, a powder mixture, a catalyst and an initiator, the powder mixture includes a ceramic powder and a sintering aid, and the premix includes an organic monomer, a cross-linking agent, a solvent, a dispersant and a pH adjuster;
[0050] A porous ceramic precursor is prepared, the ceramic slurry is poured into a mold, and then the ceramic slurry is dried and demolded to obtain a green body; the green body is subjected to cold isostatic pressing, debinding and sintering in sequence to obtain the porous ceramic precursor;
[0051] Resin infiltration, placing the porous ceramic precursor in a resin, allowing the resin to infiltrate the porous ceramic precursor, to obtain a resin-infiltrated porous ceramic precursor;
[0052] The resin-infiltrated porous ceramic precursor is subjected to warm isostatic pressing to obtain a ceramic-based composite material.
[0053] The present application first prepares a porous ceramic precursor, and the porous structure effectively reduces its density; then resin infiltration is carried out, and the infiltrated resin can significantly improve the fracture toughness and impact resistance of the matrix without significantly increasing the density of the composite material, thereby obtaining a composite material with relatively low density and excellent fracture toughness and impact resistance.
[0054] In an optional embodiment, the ceramic powder is selected from at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide and zirconium oxide; the ceramic back cover is mostly made of zirconium oxide. In the embodiment of the present application, the raw material selection is wider.
[0055] and / or, the sintering aid is selected from at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide and strontium oxide;
[0056] And / or, in the powder mixture, the mass fraction of the ceramic powder is 92wt.% to 100wt.%;
[0057] and / or, the particle size of the powder mixture is 0.9 μm to 25 μm;
[0058] And / or, the preparation of the powder mixture includes: ball milling and drying a mixture including the ceramic powder, a sintering aid and a ball milling aid to obtain the powder mixture; in the ball milling step, the mass ratio of the grinding balls, the powder mixture and the ball milling aid is 9 to 11:1:1.5 to 2.5, the ball milling speed is 180 rpm to 250 rpm, and the ball milling time is 10 to 20 hours.
[0059] In the implementation manner of the present application, the ceramic powder and the sintering aid are first ball-milled to facilitate uniform mixing of the two.
[0060] In an optional embodiment, the total mass fraction of the organic monomer and the cross-linking agent in the premix is 11wt.% to 21wt.%, the mass ratio of the organic monomer and the cross-linking agent is (10 to 23):1, the mass fraction of the dispersant is 0.3wt.% to 3.5wt.%, the mass fraction of the catalyst is 0.01wt.% to 0.10wt.%, and the pH value of the premix is 9 to 12;
[0061] And / or, the organic monomer is selected from at least one of dimethyl acrylamide and isobutylene-maleic anhydride copolymer;
[0062] And / or, the cross-linking agent is selected from at least one of methylenebisacrylamide and isobutylene-maleic anhydride copolymer;
[0063] and / or, the dispersant is selected from at least one of ammonium polyacrylate, polyethylene glycol and ammonium citrate;
[0064] And / or, the pH adjuster is aqueous ammonia.
[0065] In the implementation manner of the present application, the premixed liquid and the powder mixture are used in combination for injection molding, which is beneficial to improving the dimensional accuracy of the green body; since the powder mixture can be evenly mixed with the premixed liquid, it is beneficial to improve the uniformity of the green body, and thus is beneficial to the uniform distribution of pores in the prepared porous ceramic precursor.
[0066] In an optional embodiment, the mass fraction of the initiator in the ceramic slurry is 0.03wt.% to 0.16wt.%;
[0067] And / or, the mass fraction of the catalyst in the ceramic slurry is 0.01wt.% to 0.10wt.%;
[0068] And / or, the initiator is ammonium persulfate;
[0069] And / or, the catalyst is tetramethylethylenediamine;
[0070] And / or, the solid content of the ceramic slurry is 40% to 70%, for example, 40%, 50%, 60%, 70%;
[0071] And / or, the viscosity of the ceramic slurry is 30 mPa·s to 100 mPa·s;
[0072] And / or, the preparation of the ceramic slurry includes: ball milling a mixture including the powder mixture and the premixed liquid, and then adding a catalyst and an initiator to obtain the ceramic slurry.
[0073] The solid content in the ceramic slurry will affect the porosity of the porous ceramic precursor, and further affect the density, fracture toughness and impact resistance of the prepared ceramic-based composite material. The solid content of the ceramic slurry in this application is higher than that of conventional gel injection molding in order to form a rich pore structure. However, considering that if the solid content is too low, the shrinkage rate of the product will also increase, the solid content should not be too low.
[0074] In an optional embodiment, in the step of preparing the porous ceramic precursor, the ceramic slurry is first vacuum degassed, and a water-based release agent is applied to the molding surface of the mold, and then the degassed ceramic slurry is poured into the mold;
[0075] And / or, the drying temperature is 40°C to 70°C, and when the weight loss of the mold for pouring the ceramic slurry is 25% to 30%, the temperature is lowered to 30°C to 50°C, and the temperature is kept for 2 to 5 hours, and then demoulding;
[0076] And / or, during the cold isostatic pressing treatment, the applied pressure is 10 MPa to 200 MPa, and the holding time is 10 to 20 min; preferably, the applied pressure is 45 MPa to 160 MPa, for example, 45 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa;
[0077] And / or, in the debinding step, the temperature is first kept at 300-350°C for 0.5-2h, and then kept at 500-540°C for 0.5-2h, with a heating rate of 1°C / min-5°C / min;
[0078] And / or, the heating rate before sintering is 0.5℃ / min~1℃ / min, the sintering temperature is 1300℃~1550℃, and the insulation time is 2~4h; after the insulation is completed, the furnace temperature is reduced to 500℃ at 1℃ / min, and then cooled to room temperature with the furnace.
[0079] In the steps of preparing the porous ceramic precursor, before the green body debinding process, the green body needs to be subjected to cold isostatic pressing after vacuum packaging to further reduce the micropores inside the matrix, but the purpose is not to densify, but to reduce the contact area between the network structure of the porous ceramic precursor and the resin after filling the resin, and to reduce the interfacial thermal resistance caused by the difference in thermal conductivity; in addition, the pressure of cold isostatic pressing will affect the density of the porous ceramic precursor. The greater the pressure of cold isostatic pressing, the greater the density of the porous ceramic precursor and the lower the porosity, which is beneficial to increase the flexural strength of the composite material. At the same time, due to the reduction in porosity, the amount of subsequent resin penetration will be reduced, which is not conducive to the improvement of fracture toughness. Therefore, the pressure of cold isostatic pressing needs to be set reasonably.
[0080] In addition, the debinding step of the embodiment of the present application adopts a segmented heating and insulation method, combined with a smaller heating rate, which is beneficial to improve the temperature uniformity of various parts of the blank and reduce the deformation or cracking of the blank caused by uneven stress distribution inside the ceramic matrix due to excessively rapid heating.
[0081] In an optional embodiment, before the resin infiltration, the porous ceramic precursor is first subjected to mechanical processing, including but not limited to CNC grinding, lapping, polishing and other processing methods.
[0082] In an optional embodiment, the resin is first degassed and then the porous ceramic precursor is placed in the resin to reduce the effect of bubbles on the fracture toughness and impact resistance of the matrix.
[0083] In an optional embodiment, the method for preparing the resin comprises: mixing a curing agent and a mixed solution for 3 hours to 4 hours to obtain the resin, wherein the mixed solution comprises at least one of dimethacrylate urethane, methyl methacrylate, polyacrylic acid or triethylene glycol dimethacrylate;
[0084] And / or, the curing agent is selected from at least one of benzoyl peroxide and butanone peroxide;
[0085] And / or, the mass fraction of benzoyl peroxide in the resin is 0.2wt.% to 1wt.%;
[0086] And / or, the mass fraction of butanone peroxide in the resin is 0.4wt.% to 2wt.%.
[0087] The thermal stability of the cured resin is improved. Some resins, such as dimethacrylate urethane, have certain toughness and can improve the bonding strength between the resin and the ceramic interface. For example, triethylene glycol dimethacrylate can provide good corrosion resistance and insulation properties.
[0088] In an optional embodiment, in the resin infiltration step, the environment in which the resin immerses the porous ceramic precursor is alternately evacuated and pressurized to promote the resin to infiltrate the porous ceramic precursor;
[0089] And / or, the vacuuming step is to vacuumize to a pressure less than 0.1 Pa;
[0090] And / or, in the pressurizing step, the pressure is increased to 1 MPa to 3 MPa and maintained for 30 min to 80 min;
[0091] And / or, the vacuuming and pressurizing steps are performed 5 to 7 times.
[0092] Specifically, in some embodiments, after the sintered porous silicon carbide ceramic precursor is placed in the resin, the stainless steel top cover is closed, the vacuum valve is opened, the vacuum pump is turned on, the vacuum is evacuated to below 0.1 Pa, and the vacuum valve is closed; then the pressure valve is opened, compressed air or inert gas is introduced, and the pressure is applied to 1MPa~3MPa, maintained for 30min~80min, preferably 34min~48min, the vent valve is closed, and the pressurization is stopped; the vacuum valve is opened, and the vacuum is evacuated to 0.1Pa; the vacuuming and pressurizing process is repeated 3 to 8 times.
[0093] The inert gas refers to a gas that does not react with the porous silicon carbide ceramic precursor or the resin under process conditions, and specifically may be nitrogen, helium, and the like.
[0094] During the resin infiltration process, the two operations of vacuuming and pressurizing are performed multiple times in cycles, which can effectively improve the ability of the resin to fill the pores of the ceramic matrix and make the resin infiltration more sufficient, which is beneficial to reducing the porosity of the composite material and improving the thermal conductivity.
[0095] In an optional embodiment, during the warm isostatic pressing treatment, the pressure applied is 90 MPa to 300 MPa, the temperature is 75° C. to 90° C., and the holding time is 2 to 4 hours.
[0096] Warm isostatic pressing treatment is beneficial to prevent the resin that penetrates into the porous ceramic precursor from flowing out of the ceramic matrix due to the capillary effect, resulting in the "sweating" phenomenon. It is beneficial to uniform color of the sample surface and to improve flexural strength, fracture toughness, hardness and thermal conductivity.
[0097] In a second aspect, the present invention provides a ceramic-based composite material prepared by the method described in any one of the aforementioned embodiments.
[0098] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0099] Embodiment 1:
[0100] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which specifically includes the following steps:
[0101] (1) 95wt.% silicon nitride powder, 2wt.% magnesium oxide and 3wt.% yttrium oxide were wet-milled, with the mass ratio of grinding balls, powder mixture and anhydrous ethanol being 10:1:2; the ball milling speed was 200rpm, and the ball milling time was set to 16h. The ball mill was placed in a drying oven, and the drying conditions were 100°C and 2.5h; the ball mill was taken out, the grinding balls and powder were poured out, and the powder mixture was obtained after sieving through a 400-mesh sieve, and then placed for use.
[0102] (2) using a magnetic stirrer to uniformly mix dimethylacrylamide (organic monomer), methylenebisacrylamide (cross-linking agent) and deionized water at room temperature, then adding ammonium polyacrylate and stirring evenly, and then adding an appropriate amount of pH adjuster to adjust the pH value of the liquid to 11 to obtain a premixed solution; based on the mass of the premixed solution, the organic monomer and the cross-linking agent account for a total of 15 wt.%, the mass ratio of the organic monomer to the cross-linking agent is 20:1, and the mass fraction of ammonium polyacrylate (dispersant) is 2 wt.%.
[0103] (3) Pour the premixed liquid into a ball mill, add the prepared powder mixture, and place it in a planetary ball mill for ball milling; the ball milling speed is set to 200 r / min and the time is 5 h; a slurry with a solid content of 50% is obtained.
[0104] (4) The mold is placed in deionized water for ultrasonic cleaning. After being taken out and dried, a water-based release agent is evenly applied on the molding surface of the mold.
[0105] (5) After taking out the slurry with a solid content of 50%, add 0.05wt.% (based on the total mass of the slurry) of tetramethylethylenediamine (catalyst) and 0.12wt.% (based on the total mass of the slurry) of ammonium persulfate (initiator) to the slurry, stir evenly, remove bubbles, and pour into a mold; put the mold into a drying oven, set the temperature to 60°C and keep it warm until the weight loss is 30%, then reduce the temperature to 40°C, continue to keep warm for 3h, then demold and take out to obtain a green body.
[0106] (6) The green sample was vacuum packed and placed in a cold isostatic press for isostatic pressing at 55 MPa for 20 min.
[0107] (7) The green body after isostatic pressing is placed in a muffle furnace, and the temperature is raised to 320°C at a rate of 3°C / min and kept at that temperature for 1 hour; then the temperature is raised to 500°C at a rate of 1°C / min and kept at that temperature for 1 hour, and finally the green body is cooled in the furnace to remove excess organic matter.
[0108] (8) The green body is placed in a muffle furnace, and the furnace temperature is increased to 1550°C at a rate of 1°C / min and kept at this temperature for 4 hours; after the insulation is completed, the furnace temperature is reduced to 500°C at a rate of 1°C / min, and finally cooled to room temperature with the furnace to obtain a porous ceramic precursor; the green body is taken out for use.
[0109] (9) The obtained porous ceramic precursor is subjected to CNC grinding, lapping, polishing and other processing to obtain a backplane prototype.
[0110] (10) Dimethacrylate urethane and triethylene glycol dimethacrylate were prepared in a mass ratio of 7:3, and 1 wt.% benzoyl peroxide (based on the total mass of dimethacrylate urethane and triethylene glycol dimethacrylate) was added, and stirred at room temperature for 4 h to obtain a resin for penetration.
[0111] (11) Pour the resin into a silica gel container, place the sintered and processed porous silicon carbide ceramic precursor into the resin, and place the container into a vacuum glue injection machine; close the stainless steel top cover, open the vacuum valve, start the vacuum pump, evacuate to 0.1 Pa, and close the vacuum valve; open the pressure valve, introduce compressed air to increase the pressure to 3 MPa, maintain for 35 minutes, close the vent valve, and stop pressurizing; open the vacuum valve, evacuate to 0.1 Pa; the vacuuming and pressurizing process is repeated 6 times.
[0112] (12) The infiltrated samples were vacuum packed and then subjected to warm isostatic pressing with a pressure of 125 MPa and kept at 80 °C for 2 h.
[0113] (13) Grind and polish the sample to obtain a resin-infiltrated ceramic composite back cover.
[0114] Embodiment 2:
[0115] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that the cold isostatic pressing pressure in step (6) is 100 MPa.
[0116] Embodiment 3:
[0117] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that the cold isostatic pressing pressure in step (6) is 150 MPa.
[0118] Embodiment 4:
[0119] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that in step (11), the vacuum glue injection machine is pressurized with compressed air for 40 minutes.
[0120] Embodiment 5:
[0121] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that in step (11), the vacuum glue injection machine is pressurized with compressed air for 48 minutes.
[0122] Embodiment 6:
[0123] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that the pressure applied by the warm isostatic press in step (12) is 155 MPa.
[0124] Embodiment 7:
[0125] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that the pressure applied by the warm isostatic press in step (12) is 180 MPa.
[0126] Embodiment 8:
[0127] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which differs from Embodiment 1 mainly in that 95wt.% silicon nitride powder in step (1) is replaced by 47.5wt.% silicon nitride powder and 47.5wt.% silicon carbide powder.
[0128] Embodiment 9:
[0129] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which differs from Embodiment 1 mainly in that the silicon nitride powder in step (1) is replaced by silicon carbide powder.
[0130] Embodiment 10:
[0131] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that the heating rate in step (7) is 3°C / min, the temperature is set to 500°C, kept warm for 2h, and finally cooled with the furnace.
[0132] Embodiment 11:
[0133] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from Embodiment 1 mainly in that dimethacrylate carbamate and triethylene glycol dimethacrylate in step (10) are replaced by methyl methacrylate, and the benzoyl peroxide content is 0.5wt%; after stirring evenly, the resin is subjected to an ultrasonic water bath at 45°C.
[0134] Embodiment 12:
[0135] This embodiment provides a method for preparing a ceramic-based composite material mobile phone back cover, which is different from the embodiment 1 mainly in that steps (2) and (3) are changed to: isobutylene-maleic anhydride, deionized water, powder mixture, and ammonium polyacrylate are uniformly mixed at room temperature using a magnetic stirrer; based on the total mass of the slurry, the isobutylene-maleic anhydride content is 0.45wt.%, and the ammonium polyacrylate content is 1wt.%. After being fully mixed, the mixture is poured into a ball milling jar and placed in a planetary ball mill for ball milling; the ball milling speed is set to 300r / min for 2h.
[0136] Comparative Example 1:
[0137] This comparative example provides a method for preparing a ceramic-based composite material mobile phone back cover, which differs from Example 1 mainly in that the curing process in step (12) is replaced by vacuum-packing the sample that has completed resin infiltration and placing it in a drying oven, heating it to 80°C, and keeping it warm for 12 hours.
[0138] The performance of the back cover prepared in the above embodiments and comparative examples was tested, wherein the bending strength was tested by the three-point bending method according to ISO23242:2020 standard; the fracture toughness was tested by the single-sided V-notch plate method according to ISO 21113:2018 standard; the hardness was measured by a microhardness tester according to GB / T 16534-2009 standard; and the thermal conductivity was tested by the transient plane heat source method according to GB / T 32064-2015 standard. The test results are shown in Table 1.
[0139] Table 1
[0140]
[0141] According to Table 1, the resin-infiltrated ceramic composite cover plates prepared in the above embodiments have good performance, and have high bending strength, fracture toughness, hardness and thermal conductivity.
[0142] (1) It can be seen from Examples 1, 2 and 3 that the flexural strength of the sample increases with the increase in the pressure applied by cold isostatic pressing. However, since the density also increases, the pore size in the ceramic matrix network structure decreases, resulting in a decrease in resin permeability, causing the fracture toughness to decrease by about 5%.
[0143] (2) In Example 10, the green body after debinding showed obvious warping, and cracks appeared on the surface of the composite cover plate after isostatic pressing. This shows that the segmented heating and heat preservation setting in the debinding process and the slowing down of the heating rate can improve the uniformity of the temperature field in various parts of the sample and avoid the internal stress generated by the inconsistent shrinkage rate inside the ceramic matrix from causing adverse effects on subsequent processes.
[0144] (3) It can be seen from Example 1 and Comparative Example 1 that when curing is performed without pressure, the infiltrated resin will flow out of the ceramic matrix due to the capillary effect, resulting in a "sweating" phenomenon, which makes the sample surface color uneven and also affects the overall performance of the sample.
[0145] (4) It can be seen from Example 1, Examples 4-7 and Comparative Example 1 that the thermal conductivity of the sample is related to the pressure applied by warm isostatic pressing and the time of resin penetration; the greater the applied pressure and the longer the penetration time, the tighter and stronger the interfacial bonding between the resin and the ceramic matrix, which can reduce the gaps between the interfaces and avoid the appearance of a large number of resin-air and ceramic-air interfaces, thereby reducing the interfacial thermal resistance inside the cover plate.
[0146] (5) It can be seen from Example 1, Example 8, and Example 9 that the mechanical properties and thermal conductivity of the samples are related to the composition of the ceramic powder. The higher the silicon carbide content in the sample, the higher the hardness and thermal conductivity, but the flexural strength will decrease slightly.
[0147] (6) Generally, the thermal conductivity of zirconia ceramic backboards is about 5W / m·K to 6W / m·K, while the thermal conductivity of backboards prepared from silicon nitride, silicon carbide, and silicon nitride + silicon carbide raw materials can reach 54W / m·K to 62W / m·K, while also having good mechanical properties; therefore, the resin-infiltrated ceramic composite backboard prepared using the method of the present invention has broad application prospects.
[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic-based composite material, characterized in that: include: Prepare a ceramic slurry, wherein the ceramic slurry includes a premix, a powder mixture, a catalyst and an initiator, the powder mixture includes a ceramic powder and a sintering aid, and the premix includes an organic monomer, a cross-linking agent, a solvent, a dispersant and a pH adjuster; A porous ceramic precursor is prepared, the ceramic slurry is poured into a mold, and then the ceramic slurry is dried and demolded to obtain a green body; the green body is subjected to cold isostatic pressing, debinding and sintering in sequence to obtain the porous ceramic precursor; Resin infiltration, placing the porous ceramic precursor in a resin, allowing the resin to infiltrate the porous ceramic precursor, to obtain a resin-infiltrated porous ceramic precursor; The resin-infiltrated porous ceramic precursor is subjected to warm isostatic pressing to obtain a ceramic-based composite material.
2. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: The ceramic powder is selected from at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide and zirconium oxide; and / or, the sintering aid is selected from at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide and strontium oxide; And / or, in the powder mixture, the mass fraction of the ceramic powder is 92wt.% to 100wt.%; and / or, the particle size of the powder mixture is 0.9 μm to 25 μm; And / or, the preparation of the powder mixture includes: ball milling and drying a mixture including the ceramic powder, a sintering aid and a ball milling aid to obtain the powder mixture; in the ball milling step, the mass ratio of the grinding balls, the powder mixture and the ball milling aid is 9 to 11:1:1.5 to 2.5, the ball milling speed is 180 rpm to 250 rpm, and the ball milling time is 10 to 20 hours.
3. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: The total mass fraction of the organic monomer and the crosslinking agent in the premix is 11wt.% to 21wt.%, the mass ratio of the organic monomer and the crosslinking agent is (10-23):1, the mass fraction of the dispersant is 0.3wt.% to 3.5wt.%, the mass fraction of the catalyst is 0.01wt.% to 0.10wt.%, and the pH value of the premix is 9-12; And / or, the organic monomer is selected from at least one of dimethyl acrylamide and isobutylene-maleic anhydride copolymer; And / or, the cross-linking agent is selected from at least one of methylenebisacrylamide and isobutylene-maleic anhydride copolymer; and / or, the dispersant is selected from at least one of ammonium polyacrylate, polyethylene glycol and ammonium citrate; And / or, the pH adjuster is aqueous ammonia.
4. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: The mass fraction of the initiator in the ceramic slurry is 0.03wt.% to 0.16wt.%; And / or, the mass fraction of the catalyst in the ceramic slurry is 0.01wt.% to 0.10wt.%; And / or, the initiator is ammonium persulfate; And / or, the catalyst is tetramethylethylenediamine; And / or, the solid content of the ceramic slurry is 40% to 70%; And / or, the viscosity of the ceramic slurry is 30 mPa·s to 100 mPa·s; And / or, the preparation of the ceramic slurry includes: ball milling a mixture including the powder mixture and the premixed liquid, and then adding a catalyst and an initiator to obtain the ceramic slurry.
5. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: In the step of preparing the porous ceramic precursor, the ceramic slurry is first vacuum degassed, a water-based release agent is applied to the molding surface of the mold, and then the degassed ceramic slurry is poured into the mold; And / or, the drying temperature is 40°C to 70°C, and when the weight loss of the mold for pouring the ceramic slurry is 25% to 30%, the temperature is lowered to 30°C to 50°C, and the temperature is kept for 2 to 5 hours, and then demoulding; And / or, during the cold isostatic pressing treatment, the applied pressure is 10 MPa to 200 MPa, and the holding time is 10 min to 20 min; preferably, the applied pressure is 45 MPa to 160 MPa; And / or, in the debinding step, the temperature is first kept at 300-350°C for 0.5-2h, and then kept at 500-540°C for 0.5-2h, with a heating rate of 1°C / min-5°C / min; And / or, the heating rate before sintering is 0.5℃ / min~1℃ / min, the sintering temperature is 1300℃~1550℃, and the insulation time is 2~4h; after the insulation is completed, the furnace temperature is reduced to 500℃ at 1℃ / min, and then cooled to room temperature with the furnace.
6. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: Prior to resin infiltration, the porous ceramic precursor is mechanically processed; And / or, the resin is first degassed and then the porous ceramic precursor is placed in the resin.
7. The method for preparing a ceramic-based composite material according to claim 1, characterized in that: The preparation method of the resin comprises: mixing a curing agent and a mixed solution for 3 to 4 hours to obtain the resin, wherein the mixed solution comprises at least one of dimethacrylate carbamate, methyl methacrylate, polyacrylic acid or triethylene glycol dimethacrylate; And / or, the curing agent is selected from at least one of benzoyl peroxide and butanone peroxide; And / or, the mass fraction of benzoyl peroxide in the resin is 0.2wt.% to 1wt.%; And / or, the mass fraction of butanone peroxide in the resin is 0.4wt.% to 2wt.%.
8. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: In the resin infiltration step, the environment in which the resin immerses the porous ceramic precursor is alternately evacuated and pressurized to promote the resin to infiltrate the porous ceramic precursor; And / or, the vacuuming step is to vacuumize to a pressure less than 0.1 Pa; And / or, the pressurizing step is to pressurize to a pressure of 1 MPa to 3 MPa and maintain for 30 min to 80 min; And / or, the vacuuming and pressurizing steps are performed 5 to 7 times.
9. The method for preparing a ceramic matrix composite material according to claim 1, characterized in that: During the warm isostatic pressing treatment, the applied pressure is 90MPa to 300MPa, the temperature is 75°C to 90°C, and the holding time is 2h to 4h.
10. A ceramic matrix composite material, characterized in that: The method is prepared by any one of claims 1 to 9.